Large Eddy Simulation of Shallow Cumulus Clouds in the Southern Great Plains With an Interactive Land Surface Model - Jake J. Gristey; Graham Feingold; Wayne M. Angevine; Yao‐Sheng Chen (Journal of Advances in Modeling Earth Systems)
Abstract Shallow cumulus clouds are ubiquitous over continental land masses in summertime. They impart complex patterns of solar heating on the surface below. These patterns are dominated by cloud shadows, which drive spatial variability in the surface latent and sensible heat fluxes via the surface energy balance. This, in‐turn, generates spatial variability in buoyancy that has been suggested to modulate cloud evolution. Despite the coupling between the land surface and clouds, it is commonplace to model continental shallow cumulus clouds with large eddy simulation (LES) using spatially‐uniform prescribed surface heat fluxes. Here we present new LES of shallow cumulus clouds in the Southern Great Plains that are run with an interactive land surface model (LSM). The LSM is coupled to a 1D radiation scheme and therefore provides dynamic, heterogeneous surface heat fluxes that correspond to the evolving 1D surface solar heating pattern. We use this new simulation configuration to test whether spatially‐variable fluxes impact cloud field evolution, finding limited impact for a typical case study. Furthermore, we find no evidence of systematic differences in radiatively‐relevant cloud field properties when applying spatially‐variable fluxes across 14 simulated cases. We therefore conclude that the heterogeneity of surface fluxes due to 1D cloud shading is insufficient to influence cloud evolution. This finding agrees with previously documented length scales of static surface heterogeneities required to develop secondary circulations that can influence cloud evolution, and provides a renewed focus for mechanistic understanding of recently reported large responses in cloud evolution when invoking 3D radiation.